Impacts of Marriage Legalization on the Experiences of Sexual Minority Women in Work and Community Contexts. Issue 3 (27th May 2019) - Wootton, Angie R.; Drabble, Laurie A.; Riggle, Ellen D.B.; Veldhuis, Cindy B.; Bitcon, Caitlin; Trocki, Karen F.; Hughes, Tonda L.
ABSTRACT: The extension of marriage rights to same-sex couples in the United States provides an opportunity to examine how legalization of same-sex marriage has impacted the experiences of sexual minority women (SMW) in interactions within their extended social networks and local communities. Interviews were conducted with 20 SMW ranging in age from 23 to 75, with varying relationship statuses, and in different regions of the United States. Inductive thematic analysis of responses revealed both positive and negative/neutral impacts in 3 broad thematic areas: workplace dynamics and interpersonal interactions in the workplace, social interactions in extended social networks and local communities, and community climate and queer communities. Findings of the study underscore the importance of evaluating the impact of same-sex marriage legalization in the context of local social and political climates.